2015
DOI: 10.1109/tps.2015.2453337
|View full text |Cite
|
Sign up to set email alerts
|

Current Transmission Efficiency for Conical Magnetically Insulated Transmission Line on a 1.0-MV Linear Transformer Driver System

Abstract: Current transmission efficiency in a conical transition magnetically insulated transmission line (MITL) has been studied experimentally on a 1.0-MV linear transformer driver system, which has 10 identical cavities connected in series with MITL. Transmission efficiencies of anode current as high as 98.4% and 93.1% could be achieved when the MITL operates at load-limited and self-limited flows, respectively. As for the cathode current, because of the sufficient length of conical transition MITL, cathode current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The common-mode noise added to the B-dot sensors output signals is higher than that of B-dot monitors on the outer conductor which are at the ground potential. In fact, previous experiments conducted on the negative polarity 1.0 MV-LTD machine also suggested that the performance of the B-dot monitors on the inner electrode was usually not as perfect as those on the outer conductor [43]. However, the amplitudes of the load current given by the two groups of B-dot sensors are also in line with each other very well, and the peak value is about 108.0 kA.…”
Section: Experiments and Circuit Simulation Resultsmentioning
confidence: 79%
“…The common-mode noise added to the B-dot sensors output signals is higher than that of B-dot monitors on the outer conductor which are at the ground potential. In fact, previous experiments conducted on the negative polarity 1.0 MV-LTD machine also suggested that the performance of the B-dot monitors on the inner electrode was usually not as perfect as those on the outer conductor [43]. However, the amplitudes of the load current given by the two groups of B-dot sensors are also in line with each other very well, and the peak value is about 108.0 kA.…”
Section: Experiments and Circuit Simulation Resultsmentioning
confidence: 79%
“…There is electron current loss to the walls along downstream cylindrical MITL prior to the edge where the entire current is shunted to the anode wall as anode current. 19,21,22 In addition, the electron loss front will cut down the pulse width. The cathode current amplitudes of the PIC simulation by probes P1, P2, P3, P4, P5 and P6 are 0.97 MA, 0.86 MA, 0.78 MA, 0.77 MA, 0.77 MA, 0.38 MA.…”
Section: A Downstream Mitl Work On Self-limited Flowmentioning
confidence: 99%
“…The prime power source of such a machine may consist of a system of linear transformer drivers (LTDs) [7][8][9][10][11][12][13][14][15][16][17][18] fast Marx generators (FMGs) [7,9,[19][20][21][22] or impedance-matched Marx generators (IMGs) [18,23,24]. The pulsed power community has been developing LTD technology for 20 years on various single-cavity experiments [16,[25][26][27][28][29][30][31][32][33][34][35][36][37], multicavity (single "module") experiments [14,27,32,35,[38][39][40][41][42][43][44] and a few multimodule experiments [11,14]. The work presented here describes the design and performance of the first two meter...…”
Section: Introductionmentioning
confidence: 99%